Kontestasi Keberagamaan di Media Sosial: Kontra Interpretasi ‎Radikalisme di Platform Youtube - Elis Mila Rosa; Mega Puspita; Rizal Samsul Mutaqin; Zezen Zainul Ali (LPPM UIN Saizu Purwokerto, 2022)
Religious practices and understandings are not only expressed in the real world but also in cyberspace through several platforms. Social media is an alternative nowadays to spread religious ideas, one of which is through Youtube. Youtube as a platform that has several features and a wide reach is a medium used by ustadz to preach and spread religious ideas. However, the different scientific backgrounds possessed by each Ustadz and jama'ah who listened to lectures gives birth to an understanding that tends to truth claims and results in religious contestation. This paper wants to photograph the form of religious contestation on social media and the application of religious moderation for social media users. To analyze it, this study uses qualitative methods, in the process, the author uses a type of ethnographic research (ethnography) as an intermediary in finding available data on digital traces as well as literature (library research). This study focuses on some of the content in the Youtube account of Al-Bahjah and Khalid Basalamah Official as a data source, and the data obtained will be narrated descriptively. This research departs from the argument that in practice or understanding, it does not just appear out of nowhere. The phenomenon of religious contestation has internal and external factors that shape religious life and religious moderation as a solution to the existing phenomenon.